Integrating social science into conservation planning. (October 2021) - Niemiec, Rebecca M.; Gruby, Rebecca; Quartuch, Michael; Cavaliere, Christina T.; Teel, Tara L.; Crooks, Kevin; Salerno, Jonathan; Solomon, Jennifer N.; Jones, Kelly W.; Gavin, Michael; Lavoie, Anna; Stronza, Amanda; et al.
Abstract: A growing body of literature has highlighted the value of social science for conservation, yet the diverse approaches of the social sciences are still inconsistently incorporated in conservation initiatives. Building greater capacity for social science integration in conservation requires frameworks and case studies that provide concrete guidance and specific examples. To address this need, we have developed a framework aimed at expanding the role for social science in formal conservation planning processes. Our framework illustrates multiple ways in which social science research can contribute to four stages of such processes: 1) defining the problem and project team; 2) defining goals; 3) identifying impact pathways and designing interventions; and 4) developing and evaluating indicators of success (or failure). We then present a timely case study of wolf reintroduction in Colorado, U.S.A., to demonstrate the opportunities, challenges, and complexities of applying our framework in practice. Highlights: Clear guidance is lacking on how to apply diverse social science approaches throughout conservation planning processes. Our framework aims to expand the role for social science in four stages of formal conservation planning processes. Our case study of wolf reintroduction in Colorado demonstrates the complexities of applying our framework in practice.